Mechanical efficiency in children with different body weight: a longitudinal assessment of the quality cohort - G Jabbour; A Tremblay; M Henderson; M-E Mathieu (Termedia Publishing House, 2016)
Net mechanical efficiency (MEnet), which reflects the body's ability to transfer energy above resting levels in external work, is similar in young children regardless of their body weights. However, it is unclear whether MEnet remains stable during growth and maturation. We sought to determine whether net mechanical efficiency (MEnet) changes over a period of 3 years in children and to identify the factors associated with possible changes. A total of 169 children participating in the QUALITY (Quebec Adipose and Lifestyle InvesTigation in Youth) cohort completed an incremental cycling test, resulting in the same maximal power output during both visits. For MEnet, resting energy consumption was subtracted from total energy consumption at each exercise stage. Physical activity was measured using an accelerometer worn for 7 days. Participants were measured at year one and again two years later. MEnet did not differ across the visits at the 25, 50 and 75 watt stages. However, the participants exhibited lower MEnet values at follow-up for the 100 and 125 W stages (23(3) vs. 20(1)%; 25(4) vs. 20(2)%; p<0.01). Declines in MEnet correlated positively with declines in moderate-to-vigorous physical activity levels (r=0.78, p<0.05). The declines in moderate-to-vigorous physical activity levels across the visits were identified as significant predictors of MEnet changes at 100 and 125 W over 3 years, accounting for 22% of the relationship. In children, MEnet, determined at high exercise intensity, decreases within a period of three years, and the decrement appeared to be related to moderate-to-vigorous physical activity.